1984
DOI: 10.1083/jcb.98.4.1580
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous mammalian lectin localized extracellularly in lung elastic fibers

Abstract: An affinity-purified antibody preparation raised against a beta- galactoside-binding lectin from bovine lung was used to localize a similar lectin in rat lung by immunofluorescence and by electron microscopy after on-grid staining visualized with colloidal gold conjugated second antibody. The endogenous mammalian lectin was found in smooth muscle cells and squamous alveolar epithelial (type I) cells and was concentrated extracellularly in elastic fibers of pulmonary parenchyma and blood vessels. The extracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 38 publications
3
33
0
Order By: Relevance
“…Isolation of RL-14.5 lectin cDNA Our previous immunocytochemical studies showed that subsets of central and peripheral neurons express a lectin of approximately 14 kDa that is recognized by antisera raised against a rat lung lectin of similar size (RL-14.5; Cerra et al, 1984;Regan et al, 1986). cDNA clones encoding a 14 kDa lectin isolated from rat lung have been isolated and sequenced (Clerch et al, 1988).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Isolation of RL-14.5 lectin cDNA Our previous immunocytochemical studies showed that subsets of central and peripheral neurons express a lectin of approximately 14 kDa that is recognized by antisera raised against a rat lung lectin of similar size (RL-14.5; Cerra et al, 1984;Regan et al, 1986). cDNA clones encoding a 14 kDa lectin isolated from rat lung have been isolated and sequenced (Clerch et al, 1988).…”
Section: Resultsmentioning
confidence: 99%
“…The Hep-2 cDNA is similar or identical to the sequence of the cDNA encoding a mouse 14 kDa lectin (Wilson et al, 1989). In addition, a XGTl 1 cDNA library constructed from embryonic day 15 rat spinal cord RNA was screened with antisera generated against the RL-14.5 lectin isolated from rat lung (Cerra et al, 1984). A series of cDNA clones identified with antibody or cDNA probes were sequenced.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In some species multiple forms of soluble lectins have been detected (3,9,10). Three acidic forms have been isolated from rat and human lung (3,10).…”
mentioning
confidence: 99%